2015
DOI: 10.1039/c5cp01607j
|View full text |Cite
|
Sign up to set email alerts
|

Co-solvent enhanced zinc oxysulfide buffer layers in Kesterite copper zinc tin selenide solar cells

Abstract: A co-solvent, dimethylsulfoxide (DMSO), is added to the aqueous chemical "bath" deposition (CBD) process used to grow ZnOS buffer layers for thin film Cu2ZnSnSe4 (CZTSe) solar cells. Device performance improves markedly as fill factors increase from 0.17 to 0.51 upon the co-solvent addition. X-ray photoelectron spectroscopy (XPS) analyses are presented for quasi-in situ CZTSe/CBD-ZnOS interfaces prepared under an inert atmosphere and yield valence band offsets equal to -1.0 eV for both ZnOS preparations. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Because of no surface Ar ion cleaning, all the O 1s peaks contain a fraction arising from C‐O bonds with binding energy of 533.3 eV, which should be attributed to the organic contamination. The other peaks appearing in the untreated sample are assigned as Zn(OH) 2 (532.7 eV), Zn(O,S) alloy (531.7 eV), and ZnO (530.4 eV), respectively . Besides the Zn(O,S) alloy, the untreated Zn(O,S) film is rich in ZnO and Zn(OH) 2 , as a result of competition growth of Zinc hydroxide and Zinc ammonium complex .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of no surface Ar ion cleaning, all the O 1s peaks contain a fraction arising from C‐O bonds with binding energy of 533.3 eV, which should be attributed to the organic contamination. The other peaks appearing in the untreated sample are assigned as Zn(OH) 2 (532.7 eV), Zn(O,S) alloy (531.7 eV), and ZnO (530.4 eV), respectively . Besides the Zn(O,S) alloy, the untreated Zn(O,S) film is rich in ZnO and Zn(OH) 2 , as a result of competition growth of Zinc hydroxide and Zinc ammonium complex .…”
Section: Resultsmentioning
confidence: 99%
“…Application of Zn(O,S) buffer layer in kesterite‐based thin film solar cells also attracts increasing attention. Several institutes have reported ∼5% efficiency kesterite solar cells based on CBD‐Zn(O,S) buffer layer . Recently, M. Neuschitzer et al reported a 6.5% efficiency CZTSe solar cell which is close to the 6.9% efficiency CdS reference by adjusting the sulfur content in ultra thin CBD‐Zn(O,S) buffer layers which are less than 10 nm .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…8 Moreover, spectroscopic characterization of Cu 2 ZnSnSe 4 /ZnOS heterojunctions showed that including DMSO during CBD growth of ZnOS affected the band energy line up but resulted in no definitive compositional changes. 9 Films shown in Figure 1 were deposited with standard CBD of ZnOS on quartz substrates in an open reaction vessel that is similar for solar cell buffer layer depositions. Films grown on the quartz slides exhibit different coverage resulting in the distinctly different transmission spectra.…”
mentioning
confidence: 99%